Applied Fluid Mechanics Lab Manual - Ahmari, Habib; Md Imran Kabir, Shah; Bowers, Ginny; Open Textbook Library (Open Textbook Library, 2019)
This lab manual provides students with the theory, practical applications, objectives, and laboratory procedure of ten experiments. The manual also includes educational videos showing how student should run each experiment and a workbook for organizing data collected in the lab and preparing result tables and charts.
Experiment #1: Hydrostatic Pressure -- Experiment #2: Bernoulli's Theorem Demonstration -- Experiment #3: Energy Loss in Pipe Fittings -- Experiment #4: Energy Loss in Pipes -- Experiment #5: Impact of a Jet -- Experiment #6: Orifice and Free Jet Flow -- Experiment #7: Osborne Reynolds' Demonstration -- Experiment #8: Free and Forced Vortices -- Experiment #9: Flow Over Weirs -- Experiment #10: Pumps -- References
In English.
Description based on print resource
Keywords: Materials Science -- Textbooks